The correlation between T-wave abnormalities and adverse cardiovascular events and echocardiographic changes in hypertensive patients - Shengnan Liu; Chao Zhang; Jing Wan (Clinical and Experimental Hypertension, 2023)
Background: Major adverse cardiovascular events (MACE) are common in patients with hypertension and are associated with higher mortality. Methods: This study aimed to observe the incidence of MACE in hypertensive patients and the correlation between the electrocardiogram (ECG) T-wave abnormalities and echocardiographic changes. This retrospective cohort study analyzed the incidence of adverse cardiovascular events and changes in echocardiographic features in 430 hypertensive patients admitted to Zhongnan Hospital of Wuhan University from January 2016 to January 2022. Patients were grouped according to a diagnosis of electrocardiographic T-wave abnormalities. Results: Compared with the normal T-wave group, the incidence of adverse cardiovascular events was significantly higher in hypertensive patients with abnormal T-wave (141 [54.9%] vs 120 [69.4%], x^2 = 9.113, P = .003). However, Kaplan-Meier survival curve showed that no survival advantage was observed in the normal T-wave group at all in the hypertensive patients (P = .83). Echocardiographic values associated with cardiac structural markers, including ascending aorta diameter (AAO), left atrial diameter (LA), and interventricular septal thickness (IVS), were significantly higher in the group with abnormal T-wave than those in the group with normal T-wave at baseline and follow-up (P <.05 for all). In addition, in an exploratory Cox regression analysis model stratified by clinical characteristics of hypertensive patients, the forest plot indicated that the variables, including the age (>65 years), hypertension history (>5 years), premature atrial beats, and severe valvular regurgitation were significantly associated with adverse cardiovascular events (P <.05). Conclusion: Hypertensive patients with abnormal T-wave show a higher incidence of adverse cardiovascular events. The values of cardiac structural markers were significantly higher in the group with abnormal T-wave.